Relationship of Handgrip Strength, Asymmetries, and Calf Circumference with Functional Capacity in Individuals with Intellectual Disabilities: An Age Group Analysis - Farias-Valenzuela, C; De Moraes-Ferrari, G; Castillo-Paredes, A (BioMed Central Ltd, 2025)
Background: Handgrip strength (HGS) and calf circumference (CC) are key health markers associated with dynapenia and autonomy in the general population. However, their association with functional capacity in individuals with intellectual disabilities (ID) remains unclear. This study aimed to determine the relationship between absolute and relative HGS, upper-limb strength asymmetries, and CC with functional capacity in individuals with ID. Methods: A total of 102 individuals ([31 children: mean age = 9.58 years, SD:1.82]; [30 adolescents: mean age = 14.67 years, SD: 1.34]; [41 adults: mean age = 23.56 years, SD: 5.59]) with mild to moderate ID, from four special education schools in Santiago, Chile, were assessed. HGS and asymmetries were evaluated using dynamometry, while CC was measured anthropometrically. Functional capacity was assessed using the timed up and go (TUG), 5-repetition sit-to-stand (5R-STS), 4 × 10 m agility, and countermovement jump (CMJ) tests. Pearson, Spearman, and linear regression analyses, were applied to examine the relationships. Results: The mean values for absolute HGS, relative HGS, absolute asymmetry, percentage asymmetry, and CC were 20.71 kg, 0.35, 1.39 kg, 13.61%, and 33.89 cm, respectively. Functional test averages were 6.51 s (TUG), 10.46 s (5R-STS), 19.43 s (4 × 10 m agility), and 12.47 cm (CMJ). Significant correlations were found between absolute and relative HGS with all functional tests across age groups. Absolute HGS asymmetries correlated with some functional tests in children and adolescents, while percentage asymmetry and CC showed no associations. The very high age-group-specific correlations were TUG (r = -0.73; β = -0.34; R2 = 0.66) in children, agility 4 × 10 m test (r = -0.73; β = -0.26; R2 = 0.66) in adolescents, and CMJ (r = 0.71; β = 27.30; R2 = 0.71) in adults. Conclusions: Absolute and relative HGS, as well as absolute asymmetries, are key predictors of functional capacity in individuals with ID. Implementing strength training interventions from an early school age is critical to preserving functional capacity in this population. Clinical trial: Not applicable. © The Author(s) 2025.